Improving access to family planning services through community pharmacies: Experience from The Challenge Initiative in three counties in Kenya - Aloo, Nancy; Nyachae, Paul; Mbugua, Njeri; Sirera, Morine; Owino, Kenneth; Kagwe, Peter; Nyamu, Njeri; Hanif, Mohammed; Ndirangu, Miriam (Frontiers in Global Women's Health, 2023)
Pharmacies play a vital role in improving access to family planning (FP) services in urban areas. They complement the resource-limited public health system and are viewed as key access points for contraceptives among young people (10-24 years) and the general population. The Challenge Initiative East Africa (TCI EA), in collaboration with the health management teams of Mombasa, Kilifi, and the Nairobi Counties in Kenya and the Kenya Pharmaceutical Association (KPA) piloted an innovative public-private partnership (PPP) engagement to improve access to quality FP services offered at pharmacies in urban areas. The pilot project built the capacity of pharmacists, strengthened the referral system to the public health facilities, and made FP data accessible and visible to drive informed decision-making. This paper describes the strategies employed and outcomes. The initiative targeted 150 pharmacies across the three counties in June 2019 to December 2020 period. Our assessment shows that this intervention delivered FP commodities to 43,632 FP client visits; 71% for female clients and 21% for male. Adjusting for couple years of protection and seasonality, this translates to about 2,800 annual FP clients obtaining modern contraception in a 12-month period, including 48% injectables, 25% oral contraception, 24% emergency contraception and 3% condoms. The majority of clients (75%) were older than 24 years, 21% were 20-24 years, 3% were 15-19 years, and 1% were less than 15 years. In addition, 327 clients were referred to a public sector facility for other methods. This intervention demonstrates the potential of pharmacies in contributing to FP uptake and provides a framework for improving access to quality FP services by pharmacies. There is potential to scale such an approach beyond the 3 counties, given the involvement and reach of KPA and the Ministry of Health (MoH) health management teams.